Model moderasi beragama di era digital: Analisis interaksi santri dan kiai melalui media sosial - Aziz, Abd (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
The development of the digital era poses challenges for Islamic boarding schools in maintaining the authority of religious leaders while expanding the dissemination of religious moderation values. Until now, Islamic boarding schools have been synonymous with face-to-face communication, while religious leaders, as authoritative figures, rarely engage directly in social media. This situation raises the question of how the message of moderation from religious leaders can continue to be present and internalized by the digital community. This study aims to analyze the patterns of interaction between kiai and santri in the distribution of messages of moderation through social media. The method used is qualitative with a communication ethnography approach. Data was obtained through in-depth interviews with santri and the Information and Communication Bureau administrators, observation of digital da'wah activities, and documentation of posts from the official accounts of pesantren and santri on WhatsApp, Instagram, and Telegram. The results of the study show that clerics do not have personal accounts and do not respond directly to digital audiences, but instead convey messages through religious lectures and live broadcasts. These messages are then mediated by the Communication and Information Bureau and santri, who select, edit, and disseminate excerpts from the lectures on social media. This pattern forms a model of indirect authority, in which santri act as digital mediators who strengthen and expand the influence of kiai. This process demonstrates the transformation of pesantren communication from traditional to digital spaces, without reducing the legitimacy of kiai authority. The conclusion of this study confirms that religious moderation in Islamic boarding schools in the digital era occurs through a mediation mechanism, not through the direct participation of the kiai. These findings contribute theoretically by introducing the concept of “indirect authority” and, practically, provide a basis for Islamic boarding schools and the Ministry of Religious Affairs to strengthen the digital literacy of santri and media bureaus as effective agents of moderate da'wah.